Pemanfaatan Social Media Marketing Tools Sebagai Sarana Pemasaran Produk UMKM - Laqma Dica Fitrani; Yudha Herlambang C.P; Nurul Hasanah U.D; Linda Purnamasari; Gunasti Hudiwinarsih; Abdullah Khoir Riqqoh (Jurnal Pengabdian UNDIKMA, 2023)
This community service activity aims to increase the skills and knowledge of FnF MSMEs regarding the application of Social Media Marketing Tools as a means of online business marketing. The community service team provides training on social media marketing by utilizing the WA Business and Instagram Business applications. The stages of implementing community service include preparation, implementation, practice, and evaluation. This activity was carried out at Perbanas Hayam Wuruk University and was attended by FnF UMKM owners. The implementation activity contained two training sessions, the first was training related to WA Business, and the second was Instagram Business. The results of this community service showed a 100% increase based on the knowledge identified from the pretest and posttest evaluation results. Besides that, FnF UMKM had skills in managing WA Business and Instagram Business as online social media to support the marketing of their superior products.